Analisis Data Tanaman Padi di Indonesia Menggunakan Power BI - Ridho Darman (P3M Politeknik Negeri Bengkalis, 2018)
Rice plants are the most important plant because they are a staple food source for Indonesian people. The population growth is quite large and followed by an uneven level of rice production is certainly a serious problem for Indonesia in meeting national food needs. Information on government policies in the development of rice commodities is very important because these commodities have an important role in maintaining the stability of national food needs. BPS - Statistics Indonesia is an institution that has a variety of census and survey data in very large sizes. So that the data can be processed into more valuable information, a business intelligence application is needed that can visualize the data so that it can display regional information with high and low rice production and productivity. This data grouping aims to facilitate users in obtaining information about the production and productivity of rice plants in each region in Indonesia so that it can be a reference for the Ministry of Agriculture in the formulation and stipulation of policies in the field of agricultural infrastructure and facilities, increasing rice production and other agriculture. In this study, one of the business intelligence software was used to classify the rice crop data and its visualization. Tanaman padi merupakan tanaman yang paling penting karena merupakan sumber makanan pokok masyarakat Indonesia. Pertumbuhan penduduk yang cukup besar dan diikuti dengan tingkat produksi padi yang tidak merata tentu menjadi masalah serius bagi Indonesia dalam mencukupi kebutuhan pangan nasional. Informasi kebijakan pemerintah dalam pengembangan komoditas padi sangatlah penting karena komoditas ini memiliki peran penting dalam menjaga stabilitas kebutuhan pangan nasional. Badan Pusat Statistik adalah lembaga yang memiliki berbagai data sensus dan survei dalam ukuran yang sangat besar. Agar data tersebut dapat diolah menjadi informasi yang lebih bernilai dibutuhkan sebuah aplikasi business intelligence yang dapat memvisualisasikan data-data tersebut sehingga dapat menampilkan informasi daerah dengan produksi dan produktivitas padi yang tinggi maupun yang rendah. Pengelompokan data ini bertujuan untuk mempermudah pengguna dalam mendapatkan informasi mengenai produksi dan produktivitas tanaman padi di setiap daerah di Indonesia sehingga dapat menjadi acuan bagi Kementerian Pertanian dalam perumusan dan penetapan kebijakan di bidang penyediaan prasarana dan sarana pertanian, peningkatan produksi padi dan pertanian lainnya. Pada penelitian ini digunakan salah satu business intelligence software untuk dapat mengelompokkan data tanaman padi serta visualisasinya